How can smartphones bring about a developmental breakthrough in school education? - Nirupam Bajpai; Anchal Sharma (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2022)
India being the second-highest producer of smartphones in the world, has been exploring ways to make the digital tool reach everyone. With the availability of a variety of low-cost smartphones and affordable internet data plans, the country has witnessed a substantial increase in the ownership of smartphones. This penetration has not been limited to the urban peripherals of the country but the rural areas as well. India's rural internet user base has grown over three times faster and is quickly catching up to surpass the urban user base. The opportunity must be utilized well by the government, as the growth and familiarity of rural India with smartphones make it an ideal platform to deliver information and services that encompass the ecosystem of the digital divide. Smartphones in the field of education have already been widely disseminated, with enormous potential for future growth. Low-cost smartphones with the features like high speed, affordable internet, pre-installed applications, and audio-assistant features, can prove revolutionary in the transformational journey. The digital tool is foreseen to bring the latest ed-tech advancements in the education sector, especially in rural India. Smartphones hold the potential to support the Anganwadi workers, teachers, and school nutrition program, by introducing new and effective ways of functioning. This will play a big role in supporting early education, primary & secondary education, and teachers' continuous development, especially at the grass-root level. This paper explores how smartphones have been and can further support the public school system in the country
Keywords: 330; Mobiltelefon; Mobile Anwendung; E-Learning; Schule; Frühkindliche Bildung; Bildungschancen; Indien